Power capacitor and preparation method thereof
By optimizing the preparation process and materials of aluminum electrolytic capacitors, the stability of aluminum electrolytic capacitors in extreme environments is solved by using high-purity water and specific boric acid system-based liquid, modified cellulose fibers and bistrifluoromethanesulfonimide lithium electrolytes. Problem, capacitors with high capacitance, impact resistance and long life are achieved.
Patent Information
- Application Number
- CN202411621039.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-14
AI Technical Summary
After long-term operation, existing aluminum electrolytic capacitors have problems such as capacitance attenuation, internal temperature rise, and insulation performance decline, which cannot meet the stable performance requirements of power grid equipment in extreme environments, especially high temperature, high humidity, low temperature, and voltage resistance. The impact and vibration requirements are insufficient.
By optimizing the capacitance structure and preparation process, aluminum foil is treated with high purity water and specific boric acid system, combined with medium and high-density electrolytic paper and modified cellulose fibers, electrolyte is prepared using lithium bistrifluoromethanesulfonimide and organic solvents, and adopted Double waist sealing technology improves the impact resistance and stability of the capacitor.
It significantly improves the life of the capacitor, high temperature stability and impact resistance, reduces losses, meets the stable performance requirements of power grid equipment in extreme environments, and extends the service life.
Smart Images

Figure BDA0005133439880000141 
Figure BDA0005133439880000151
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum electrolytic capacitors, and in particular relates to a power capacitor and a preparation method thereof. Background Art
[0002] Capacitors play an important role in today's electronic products, and aluminum electrolytic capacitors play an important role in the field of electronic equipment with their high capacitance, strong current handling capability, compact size, long service life, cost-effectiveness and wide applicability. They are widely used in important fields such as home appliances, mid-to-high-end power supplies, hybrid devices, and power reserves of electric motors, power factor correction, and stability of power transmission and distribution systems. They also play the role of filtering, bypassing, coupling and decoupling in circuits and help improve the efficiency and stability of industrial equipment and reduce energy consumption and costs.
[0003] Power capacitors are one of the important electronic components in power systems. They are used for reactive power compensation, voltage regulation and filtering, etc. Their performance directly affects the stability and efficiency of the power system. Nowadays, domestic power aluminum electrolytic capacitors often have problems such as large capacitance attenuation, internal temperature rise, and reduced insulation performance after long-term operation, which affects the reliability and service life of the overall equipment. However, the existing aluminum electrolytic capacitors do not meet the warranty period requirements of the State Grid and cannot fully meet the special use environment (high temperature and humidity resistance, low temperature resistance, voltage shock resistance, vibration resistance)
[0004] Therefore, in order to meet the requirements of smart meters and other power grid equipment under extreme low temperature conditions, capacitors also need to maintain stable performance to avoid performance degradation or failure due to low temperature. Therefore, a new type of aluminum electrolytic capacitor is needed. The characteristics of this power capacitor are simple production process, moderate price, excellent performance under high and low temperature, resistance to external voltage impact, vibration resistance, and easy installation. Summary of the invention
[0005] The purpose of the present invention is to provide a power capacitor and a method for preparing the same. By optimizing the structure of the capacitor and the preparation process of each component and utilizing a highly reliable product enabling method, the capacitance of the power capacitor is increased, its loss is reduced, and its impact resistance is enhanced, thereby extending the service life of the capacitor and improving the longevity of power grid equipment.
[0006] A power capacitor, the raw materials for its preparation include: positive electrode foil, negative electrode foil, electrolytic paper, positive and negative guide needles, colloid particles, aluminum shell, sleeve, and electrolyte.
[0007] The positive electrode foil and the negative electrode foil are both finished aluminum foils, and the preparation method thereof comprises the following steps: boiling the aluminum foil material in high-purity water for 3 to 5 minutes, placing it in a forming liquid at a temperature of 85 to 90° C. for forming, washing it with deionized water after forming, placing it in a muffle furnace for heat treatment, and performing secondary forming to obtain the finished aluminum foil.
[0008] Preferably, the aluminum foil material can be selected from microporous aluminum foil.
[0009] Preferably, the raw materials for preparing the chemical conversion liquid include high-purity water, boric acid, ammonium pentaborate, borax, and ammonia water.
[0010] In the chemical formation liquid, the mass fraction of boric acid is 8% to 12%, the mass fraction of ammonium pentaborate is 0.05% to 0.1%, and the mass fraction of borax is 0.01% to 0.05%.
[0011] Preferably, the resistivity of the high-purity water is 15 to 20 MΩ·cm.
[0012] Preferably, the volume concentration of the ammonia water is 20% to 25%.
[0013] The preparation method of the chemical liquid comprises the following steps: dissolving boric acid, ammonium pentaborate and borax in high-purity water in sequence, adding ammonia water to adjust the pH value to 5.5-6.5, and stirring evenly to obtain the chemical liquid.
[0014] The inventors found that the use of a specific boric acid system chemical liquid can not only increase the life of the capacitor, but also improve the high temperature stability of the capacitor. This may be because on the one hand, high-purity water is used as a solvent to remove impurities that may interfere with the reaction, improve the purity of the reaction system, and help reduce unnecessary side reactions and additional heat generation; on the other hand, boric acid, ammonium pentaborate, borax and other boron-containing compounds react relatively mildly in the chemical liquid, generate little heat, and will not produce violent exothermic reactions, which can reduce the internal temperature rise during use, thereby improving the life and thermal stability of the capacitor. The use of ammonia water to adjust the pH value is not only conducive to the formation of aluminum oxide, but also avoids violent reactions and heat release caused by overacidity or overalkali. In addition, the synergistic effect between the raw materials of the specific boric acid system chemical liquid can improve the density and stability of the oxide film on the surface of the aluminum foil, thereby improving the voltage resistance of the positive and negative foils, and thus improving the life of the capacitor.
[0015] The formation step adopts a constant current and constant voltage method, first using 0.04-0.06A / cm 2 Use constant current method to convert the current density into constant voltage method for 8 to 10 minutes after the voltage reaches 490 to 510 V.
[0016] The secondary formation adopts constant current and constant pressure method, firstly using 0.04~0.06A / cm 2Use constant current method to convert the current density into constant voltage method for 3 to 5 minutes after the voltage reaches 490 to 510 V.
[0017] Preferably, the heat treatment conditions are: temperature of 480-520° C., and holding time of 1-3 min.
[0018] The electrolytic paper is a superposition of medium-density electrolytic paper and high-density electrolytic paper.
[0019] The method for preparing medium-density electrolytic paper comprises the following steps: taking bleached kraft softwood pulp, soaking it in deionized water, beating it to a beating degree of 83-87°SR, diluting it with deionized water until the mass concentration of absolute dry pulp in the system is 1.5-2.5 g / L, making wet paper, pressing and drying the wet paper, and then calendering it to obtain medium-density electrolytic paper.
[0020] The viscosity of the bleached kraft softwood pulp is 20-25CP, the ash content is ≤0.3%, the average fiber length is 2-2.5mm, and the average fiber roughness is 15-16mg / 100g; further preferably, the viscosity of the bleached kraft softwood pulp is 22CP, the ash content is 0.2%, the average fiber length is 2.29mm, and the average fiber roughness is 15.5mg / 100g.
[0021] In some preferred embodiments, the bleached kraft softwood pulp is purchased from Kellyville, Canada.
[0022] The inventors found that the use of specific bleached kraft softwood pulp as a raw material to prepare medium-density electrolytic paper can improve the capacitance and impact resistance of the capacitor. This may be because the specific bleached kraft softwood pulp can form a more uniform and dense fiber network in the electrolytic paper due to its long fibers and stable structure, which helps to increase the surface area of the electrolytic paper, thereby not only increasing the capacitance of the capacitor, but also forming a dense network that can enhance the mechanical strength of the capacitor. However, the performance improvement of the capacitor is limited.
[0023] Preferably, the wet paper making weight is 24-28 g / m 2 .
[0024] Preferably, the calendering treatment conditions are: temperature 62-66°C, pressure 0.15-0.2 kgf / cm 2 .
[0025] Preferably, the thickness of the medium-density electrolytic paper is 30 to 45 kilograms.
[0026] The preparation method of high-density electrolytic paper comprises the following steps: taking bleached kraft softwood pulp, soaking it in deionized water, beating it to a beating degree of 77-82°SR, and diluting it with first deionized water to obtain liquid one; taking modified cellulose fiber, mixing it in second deionized water, dispersing it, adding it to liquid one, homogenizing it for 2-4 hours, making wet paper, pressing and drying the wet paper, and calendering it to obtain high-density electrolytic paper.
[0027] Preferably, the mass concentration of the absolute dry pulp in the liquid one is 1.5 to 2.5 g / L.
[0028] Preferably, the added amount of the modified cellulose fiber is 1% to 3% of the mass of the absolute dry pulp.
[0029] Preferably, the mass ratio of the modified cellulose fiber to the second deionized water is 1:(100-200); further preferably, it is 1:150.
[0030] The preparation method of the modified cellulose fiber comprises the following steps: uniformly dispersing the cellulose fiber in a third deionized water, adding a modifier, adjusting the pH of the system to be stable between 10 and 10.5, reacting for 3 to 5 hours, washing the product with deionized water until it is neutral, and drying the product.
[0031] Preferably, the cellulose fibers include first cellulose fibers, second cellulose fibers and third cellulose fibers.
[0032] Preferably, the first cellulose fibers have a length of 100 to 1000 μm and a diameter of 100 to 1000 nm.
[0033] Preferably, the second cellulose fibers have a length of 1 to 20 μm and a diameter of 20 to 80 nm.
[0034] Preferably, the third cellulose fibers have a length of 200 to 800 nm and a diameter of 1 to 10 nm.
[0035] In some preferred embodiments, the first cellulose fiber, the second cellulose fiber and the third cellulose fiber are all purchased from MFC, CNF-H1 and CNC produced by Zhejiang Jinjiahao Green Nanomaterials Co., Ltd.
[0036] Preferably, the mass ratio of the first cellulose fibers, the second cellulose fibers and the third nanocellulose is 1:(1-3):(2-4); more preferably, it is 1:2:3.
[0037] Preferably, the mass ratio of the cellulose fiber to the third deionized water is 1:(150-250); further preferably, it is 1:200.
[0038] The inventors found that the high-density electrolytic paper prepared by adding three different cellulose fibers to a specific bleached kraft softwood pulp can further improve the capacitance, mechanical strength and stability of the capacitor. This may be because the introduction of three cellulose fibers with different aspect ratios can increase the complexity and diversity of the fiber structure inside the electrolytic paper. The long fibers can provide a good conductive channel to promote the rapid transmission of charge inside the electrolytic paper; the short fibers can fill the gaps between the long fibers to form a tighter fiber network, thereby improving the density and strength of the electrolytic paper. The synergistic effect of the long and short fibers enables the electrolytic paper to maintain high capacity while also having good stability and durability. During the mixing process, the fibers of the bleached kraft softwood pulp and the three cellulose fibers with different aspect ratios will interact with each other, which helps to enhance the bonding force between the fibers, so that the high-density electrolytic paper is not easy to deform or break when subjected to external forces or temperature changes, thereby maintaining stable capacitance performance. At the same time, this bonding force also helps to improve the overall mechanical strength and service life of the electrolytic paper. However, the cellulose fibers have a relatively large length diameter and poor dispersibility in the bleached kraft softwood pulp slurry, which affects the performance of the prepared high-density electrolytic paper.
[0039] Preferably, the modifier is 2,2,6,6-tetramethylpiperidinyl oxide, sodium bromide and sodium hypochlorite.
[0040] Preferably, the mass ratio of the 2,2,6,6-tetramethylpiperidinyl oxide, sodium bromide and sodium hypochlorite is 1:(4-6):(290-310); further preferably, it is 1:10:300.
[0041] Preferably, the amount of the modifier added is 5 to 8 times the mass of the cellulose fiber.
[0042] The inventors found that the use of a specific modifier to modify the cellulose fiber and the use of high-speed homogenization dispersion can improve the dispersibility of the cellulose fiber in the bleached kraft softwood pulp slurry. This may be because 2,2,6,6-tetramethylpiperidinyl oxide and sodium bromide catalyze the selective oxidation of cellulose fibers with sodium hypochlorite, which can destroy the hydrogen bond network of cellulose fibers in the amorphous region, increase the hydrophilicity and reactivity of cellulose fibers, and not only help cellulose fibers to better combine with other components in the subsequent processing process, but also help to improve the overall mechanical strength and service life of electrolytic paper, and also help to improve the absorption and retention capacity of electrolytic paper for electrolytes, and further improve the capacitance performance. On the other hand, the modification also changes the surface structure and chemical properties of cellulose fibers, thereby increasing the negative charge of cellulose fibers, helping to disperse and stabilize cellulose fibers in the slurry, reducing the agglomeration and precipitation of cellulose fibers, and thus improving the stability and durability of electrolytic paper.
[0043] Preferably, the wet paper making weight is 24-28 g / m 2 .
[0044] Preferably, the rotation speed of the high-speed homogenizer is 15000-20000 rpm.
[0045] Preferably, the calendering treatment conditions are: temperature 62-66°C, pressure 0.15-0.2 kgf / cm 2 .
[0046] Preferably, the thickness of the high-density electrolytic paper is 15 to 30 cm.
[0047] Preferably, the electrolyte comprises lithium bis(trifluoromethanesulfonyl imide) and an organic solvent.
[0048] Preferably, the concentration of the lithium bis(trifluoromethanesulfonyl)imide in the electrolyte is 0.5 to 1.5 mol / L.
[0049] Preferably, the organic solvent is a mixture of ethylene carbonate, dimethyl carbonate, propylene carbonate and N-methylpyrrolidone.
[0050] Preferably, the volume ratio of ethylene carbonate, dimethyl carbonate, propylene carbonate and N-methylpyrrolidone is (1-3):(1-3):(1-3):1; more preferably, it is 2:2:2:1.
[0051] The inventors found that the selection of specific organic solvents and lithium salts to prepare electrolytes can improve the high temperature and low temperature resistance of capacitors. This may be because there is a synergistic effect between these four organic solvents, and there is good mutual solubility and synergistic effect between ethylene carbonate and propylene carbonate. The addition of ethylene carbonate can reduce the melting point of propylene carbonate and improve the low temperature performance of the electrolyte. At the same time, the mixing of the two can form a stable solvation structure, which is conducive to the transmission and storage of ions. The use of N-methylpyrrolidone with ethylene carbonate and propylene carbonate can improve the stability of the electrolyte, promote the efficient transmission of ions, and improve the electrochemical stability of the capacitor. Dimethyl carbonate and propylene carbonate are compounded, which can not only reduce the viscosity of the electrolyte, improve ion mobility, but also reduce the melting point, which helps to improve the low temperature performance of the electrolyte. In addition, the four organic solvents can improve the wettability of the electrode surface, promote the rapid transmission of ions at the electrode / electrolyte interface, thereby improving the capacitance performance.
[0052] The preparation method of the power capacitor comprises the following steps: cutting the positive electrode foil and the negative electrode foil and riveting them with the positive guide pin and the negative guide pin; putting the electrolytic paper between the riveted positive electrode foil and the negative electrode foil and winding them to form a core package, injecting electrolyte into the core package, sealing it in an aluminum shell by using colloid particles, and performing mechanized waisting and sealing to obtain a semi-finished capacitor; washing the semi-finished capacitor, sleeve-fitting it, aging and selecting it, performing secondary aging and selecting it, observing the appearance, and inspecting it in sequence to obtain the capacitor.
[0053] Preferably, the number of layers of the electrolytic paper is 4 (medium-density electrolytic paper and high-density electrolytic paper are stacked into one layer).
[0054] Although high-density electrolytic paper has excellent performance, its processing method is more complicated and has higher cost. The inventor found that the medium-density electrolytic paper and high-density electrolytic paper are superimposed as electrolytic paper, and when assembling capacitors, when the number of plies of electrolytic paper is 4 layers, not only can cost be saved, but also ESR value (equivalent series resistance) can be reduced, and high voltage impact force can be promoted simultaneously. This may be because when medium and high-density electrolytic paper is mixed with four layers, on the one hand, the electrolytic paper of different densities has different liquid absorption performance and liquid retention capacity, and high-density electrolytic paper usually has better liquid retention capacity, while low-density electrolytic paper has better liquid absorption speed, and this combination can optimize the distribution and maintenance of electrolyte, reduce the loss and volatilization of electrolyte, thereby reduce ESR value. On the other hand, multi-layer composite structure can improve the overall fiber structure of electrolytic paper, make it more uniform and dense, contribute to reduce the pores and defects inside electrolytic paper, improve the transmission efficiency of electrolyte, further reduce ESR value, and can also enhance the pressure resistance of whole electrolytic paper structure, improve the impact force of product under high voltage.
[0055] The conditions for the aging selection and secondary aging selection are: the ambient temperature is 155° C., the applied voltage is 500V, and it is applied continuously for 12 hours. During this process, the change rate of the leakage recovery value of the capacitor is continuously monitored. If the change rate is ≤10%, the next step can be entered.
[0056] In some preferred schemes, the semi-finished capacitor is subjected to a secondary waisting and re-casing after cleaning, which can further improve the stability of the core package in the aluminum shell, prevent the internal structure from changing during use, and improve the vibration resistance of the product.
[0057] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0058] 1. The present invention provides a power capacitor which not only has a large capacity but also has good high and low temperature characteristics, strong vibration resistance, voltage shock resistance, and a long life.
[0059] 2. The present invention adopts a boric acid system with low calorific value to form aluminum foil, which reduces the internal temperature rise when the product is used, and can not only increase the life of the capacitor, but also improve the high temperature stability of the capacitor.
[0060] 3. The present invention adopts an electrolyte with low water content and high conductivity, which can improve the high temperature resistance and low temperature resistance of the product.
[0061] 4. The present invention adopts high-purity guide needles and high-voltage aluminum stems to ensure the stability of product parameter performance.
[0062] 5. The present invention adopts 4 layers of mixed medium and high density electrolytic paper to reduce the ESR value of the product and improve the high voltage impact force.
[0063] 6. The present invention adopts a special aging process to ensure that the leakage current recovery value change rate of the product within the validity period is ≤10%.
[0064] 7. The assembly process of the present invention adopts a double waist method to improve the vibration resistance of the product. DETAILED DESCRIPTION
[0065] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0066] The raw materials used in the present invention are all commercially available, specifically:
[0067] The viscosity of bleached kraft softwood pulp is 22CP, the ash content is 0.2%, the average fiber length is 2.29mm, and the average fiber roughness is 15.5mg / 100g, which is purchased from Canada Kelly. The length of the first cellulose fiber is 100-1000μm, and the diameter is 100-1000nm; the length of the second cellulose fiber is 1-20μm, and the diameter is 20-80nm; the length of the third cellulose fiber is 200-800nm, and the diameter is 1-10nm; all purchased from Zhejiang Jinjiahao Green Nanomaterials Co., Ltd., MFC, CNF-H1, CNC. Microporous aluminum foil: product model MA-EN-CU-0005, Kelude.
[0068] Example 1
[0069] The present embodiment provides a power capacitor, and the raw materials for preparing the power capacitor are: positive electrode foil, negative electrode foil, electrolytic paper, positive and negative guide pins, colloid particles, aluminum shell, casing, and electrolyte.
[0070] The positive electrode foil and the negative electrode foil are both finished aluminum foils, and the preparation method thereof comprises the following steps: boiling the microporous aluminum foil in high-purity water for 4 minutes, placing the foil in a forming liquid at a temperature of 88° C. for forming, washing the foil with deionized water after forming, placing the foil in a muffle furnace for heat treatment, and performing secondary forming to obtain the finished aluminum foil.
[0071] The raw materials for preparing the chemical liquid are high-purity water, boric acid, ammonium pentaborate, borax and ammonia water.
[0072] In the chemical forming liquid, the mass fraction of boric acid is 10%, the mass fraction of ammonium pentaborate is 0.08%, and the mass fraction of borax is 0.03%.
[0073] The resistivity of the high-purity water is 18 MΩ·cm.
[0074] The volume concentration of the ammonia water is 22%.
[0075] The preparation method of the chemical liquid comprises the following steps: dissolving boric acid, ammonium pentaborate and borax in high-purity water in sequence, adding ammonia water to adjust the pH to 6.0, and stirring evenly to obtain the chemical liquid.
[0076] The formation step adopts the constant current and constant voltage method, firstly with 0.05A / cm 2 The current density is set to constant current method, and when the voltage reaches 500 V, constant voltage method is used for 9 minutes.
[0077] The secondary formation adopts the constant current and constant voltage method, firstly with 0.05A / cm 2 The current density is set to constant current method, and when the voltage reaches 500 V, constant voltage method is used for 4 minutes.
[0078] The heat treatment conditions are: temperature of 500° C. and holding time of 2 min.
[0079] The electrolytic paper is a superposition of medium-density electrolytic paper and high-density electrolytic paper.
[0080] The method for preparing medium-density electrolytic paper comprises the following steps: taking bleached kraft softwood pulp, soaking it in deionized water, beating it to a beating degree of 85°SR, adding deionized water to dilute it to a mass concentration of absolute dry pulp in the system of 2.0 g / L, making wet paper, pressing and drying the wet paper, and then calendering it to obtain medium-density electrolytic paper.
[0081] The wet paper making weight is 26g / m 2 .
[0082] The calendering treatment conditions are: temperature 65°C, pressure 0.18 kgf / cm 2 .
[0083] The thickness of the medium density electrolytic paper is 30 kilograms.
[0084] The preparation method of high-density electrolytic paper comprises the following steps: taking bleached kraft softwood pulp, soaking it in deionized water, beating it to a beating degree of 80°SR, and diluting it with first deionized water to obtain liquid one; taking modified cellulose fiber, mixing it in second deionized water, dispersing it, adding it to liquid one, homogenizing it for 3 hours, making wet paper, pressing and drying the wet paper, and calendering it to obtain high-density electrolytic paper.
[0085] The mass concentration of the absolute dry pulp in the liquid 1 is 2.0 g / L.
[0086] The added amount of the modified cellulose fiber is 2% of the mass of the absolute dry pulp.
[0087] The mass ratio of the modified cellulose fiber to the second deionized water is 1:150.
[0088] The preparation method of the modified cellulose fiber comprises the following steps: uniformly dispersing the cellulose fiber in a third deionized water, adding a modifier, adjusting the pH of the system to be stable at about 10.3, reacting for 4 hours, washing the product with deionized water to neutrality, and drying to obtain the modified cellulose fiber.
[0089] The mass ratio of the cellulose fiber to the third deionized water is 1:200.
[0090] The modifiers are 2,2,6,6-tetramethylpiperidinyl oxide, sodium bromide and sodium hypochlorite.
[0091] The mass ratio of the 2,2,6,6-tetramethylpiperidinium oxide, sodium bromide and sodium hypochlorite is 1:10:300.
[0092] The added amount of the modifier is 6 times the mass of the cellulose fiber.
[0093] The cellulose fibers include first cellulose fibers, second cellulose fibers and third cellulose fibers.
[0094] The mass ratio of the first cellulose fibers, the second cellulose fibers and the third nanocellulose is 1:2:3.
[0095] The wet paper making weight is 26g / m 2 .
[0096] The rotation speed of the high-speed homogenizer is 18000 rpm.
[0097] The calendering treatment conditions are: temperature 65°C, pressure 0.18 kgf / cm 2 .
[0098] The thickness of the high-density electrolytic paper is 30 kilograms.
[0099] The electrolyte is lithium bis(trifluoromethanesulfonyl)imide and an organic solvent.
[0100] The concentration of the lithium bis(trifluoromethanesulfonyl)imide in the electrolyte is 1.0 mol / L.
[0101] The organic solvent is a mixture of ethylene carbonate, dimethyl carbonate, propylene carbonate and N-methylpyrrolidone.
[0102] The volume ratio of the ethylene carbonate, dimethyl carbonate, propylene carbonate and N-methylpyrrolidone is 2:2:2:1.
[0103] The preparation method of the power capacitor comprises the following steps: cutting the positive electrode foil and the negative electrode foil and riveting them with the positive guide pin and the negative guide pin; placing the electrolytic paper between the riveted positive electrode foil and the negative electrode foil and winding them to form a core package, injecting electrolyte into the core package, sealing it in an aluminum shell by using colloid particles, and performing mechanized waisting and sealing to obtain a semi-finished capacitor; washing the semi-finished capacitor, sleeve-fitting it, aging and selecting it, performing secondary aging and selecting it, observing the appearance, and inspecting it in sequence to obtain the capacitor.
[0104] The number of layers of the electrolytic paper is 4.
[0105] The conditions for the aging selection and secondary aging selection are: the ambient temperature is 155° C., the applied voltage is 500V, and it is applied continuously for 12 hours. During this process, the change rate of the leakage recovery value of the capacitor is continuously monitored. If the change rate is ≤10%, the next step can be entered.
[0106] Example 2
[0107] The difference between this embodiment and embodiment 1 is that the thickness of the medium-density electrolytic paper is 40 kilograms; the thickness of the high-density electrolytic paper is 20 kilograms; and the semi-finished capacitor is subjected to secondary waisting and re-casing after cleaning.
[0108] Example 3
[0109] The difference between this embodiment and embodiment 2 is that in the chemical formation liquid, the mass fraction of boric acid is 10%, the mass fraction of ammonium pentaborate is 0.1%, and the mass fraction of borax is 0.05%.
[0110] Comparative Example 1
[0111] The difference between this comparative example and Example 2 is that the raw materials for preparing the chemical formation liquid are high-purity water and phosphoric acid; and the mass fraction of phosphoric acid in the chemical formation liquid is 10%.
[0112] Comparative Example 2
[0113] The difference between this comparative example and Example 2 is that the raw materials for preparing the chemical formation liquid are high-purity water and boric acid; and the mass fraction of boric acid in the chemical formation liquid is 10%.
[0114] Comparative Example 3
[0115] The difference between this comparative example and Example 2 is that the viscosity of the bleached kraft softwood pulp is 20 CP, the average fiber length is 3.1 mm, and the average fiber roughness is 20 mg / 100 g.
[0116] The bleached kraft softwood pulp was purchased from Canada Goodsound, Goodsound 100.
[0117] Comparative Example 4
[0118] The difference between this comparative example and Example 2 is that the electrolytic paper is medium-density electrolytic paper.
[0119] Comparative Example 5
[0120] The difference between this comparative example and Example 2 is that the method for preparing high-density electrolytic paper comprises the following steps: taking bleached kraft softwood pulp, soaking it in deionized water, beating it to a beating degree of 80°SR, and diluting it with a first deionized water to obtain liquid one; taking cellulose fiber, mixing it in deionized water and dispersing it, adding it to liquid one, homogenizing it for 3 hours, making wet paper, pressing and drying the wet paper, and then calendering it to obtain high-density electrolytic paper.
[0121] Comparative Example 6
[0122] The difference between this comparative example and Example 2 is that the cellulose fibers are first cellulose fibers.
[0123] Comparative Example 7
[0124] The difference between this comparative example and Example 2 is that the modifiers are sodium bromide and sodium hypochlorite; and the mass ratio of the sodium bromide to the sodium hypochlorite is 1:30.
[0125] Comparative Example 8
[0126] The difference between this comparative example and Example 2 is that the number of layers of the electrolytic paper is 1.
[0127] Comparative Example 9
[0128] The difference between this comparative example and Example 2 is that the electrolyte is lithium bis(trifluoromethanesulfonyl)imide and high-purity water.
[0129] Comparative Example 10
[0130] The difference between this comparative example and Example 2 is that the organic solvent is a mixture of ethylene carbonate, dimethyl carbonate and N-methylpyrrolidone; and the volume ratio of ethylene carbonate, dimethyl carbonate and N-methylpyrrolidone is 2:2:1.
[0131] Performance Testing
[0132] The positive foil is applied with 600VF and the negative foil is applied with 3V. The capacitance, loss factor DF and leakage current LC of the power capacitor are tested according to the method in GB / T 6346.1-2024 "Fixed capacitors for electronic equipment Part 1: General specification".
[0133] Mechanical shock test: Fix the capacitor to the test equipment, with a pulse time of 6ms and an acceleration of 100g / s half-sine wave. Apply 6 times in each direction of 3 mutually perpendicular axes. After recovering for 1 to 2 hours, test the capacitance of the power capacitor. The capacitance loss rate is (initial capacitance - capacitance after test) / initial capacitance × 100%.
[0134] Vibration test: fix the capacitor to the test equipment, with a peak acceleration of 5g / s; 4 cycles in each of three directions, with a frequency from 10Hz to 2000Hz, each cycle time of 20min, a total test of 12h, and after 1~2 hours of recovery, test the capacitance of the power capacitor and calculate the capacitance loss rate.
[0135] High temperature resistance test: The capacitor was stored at 110℃ and 450V for 10,000 hours. After 1 to 2 hours of recovery, the capacitance of the power capacitor was tested and the capacitance loss rate was calculated. The results are shown in Table 1.
[0136] Table 1 Measurement results
[0137]
[0138]
[0139] According to statistics, the power capacitors prepared by Examples 1 to 3 of the present invention not only have good capacitance characteristics and large capacitance, but also have strong vibration resistance, voltage shock resistance, good high temperature characteristics, and long life. Comparative Example 1 uses phosphoric acid as the chemical liquid, Comparative Example 2 does not add ammonium pentaborate, borax, and ammonia water to the chemical liquid, Comparative Example 3 has large average fiber length and roughness, Comparative Example 4 does not add medium density electrolytic paper, Comparative Example 5 does not modify the cellulose fiber, Comparative Example 6 does not add the second cellulose fiber and the third cellulose fiber, Comparative Example 7 does not add 2,2,6,6-tetramethylpiperidin oxide, Comparative Example 8 has too few electrolytic paper layers, Comparative Example 9 has water as the electrolyte, and Comparative Example 10 has no propylene carbonate in the organic solvent. The prepared power capacitors have defects. Therefore, the power capacitors prepared by the raw materials and methods described in this application not only have large capacity, but also have good high and low temperature characteristics, strong vibration resistance, voltage shock resistance, and long life.
[0140] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A power capacitor, characterized in that: The raw materials for its preparation include: positive electrode foil, negative electrode foil, electrolytic paper, positive and negative guide needles, colloid particles, aluminum shell, casing, and electrolyte; The positive electrode foil and the negative electrode foil are both finished aluminum foils, and the preparation method thereof comprises the following steps: boiling the aluminum foil material in high-purity water for 3 to 5 minutes, placing it in a forming liquid at a temperature of 85 to 90° C. for forming, washing it with deionized water after forming, placing it in a muffle furnace for heat treatment, and performing secondary forming to obtain the finished aluminum foil. The raw materials for preparing the chemical liquid include high-purity water, boric acid, ammonium pentaborate, borax and ammonia water. In the chemical formation liquid, the mass fraction of boric acid is 8% to 12%, the mass fraction of ammonium pentaborate is 0.05% to 0.1%, and the mass fraction of borax is 0.01% to 0.05%.
2. The power capacitor according to claim 1, characterized in that: The resistivity of the high-purity water is 15 to 20 MΩ·cm.
3. The power capacitor according to claim 1, characterized in that: The electrolytic paper is a superposition of medium-density electrolytic paper and high-density electrolytic paper.
4. The power capacitor according to claim 3, characterized in that: The method for preparing medium-density electrolytic paper comprises the following steps: taking bleached kraft softwood pulp, soaking it in deionized water, beating it to a beating degree of 83-87°SR, diluting it with deionized water until the mass concentration of absolute dry pulp in the system is 1.5-2.5 g / L, making wet paper, pressing and drying the wet paper, and then calendering it to obtain medium-density electrolytic paper.
5. The power capacitor according to claim 4, characterized in that: The bleached kraft softwood pulp has a viscosity of 20-25 CP, an ash content of ≤0.3%, an average fiber length of 2-2.5 mm, and an average fiber roughness of 15-16 mg / 100 g.
6. The power capacitor according to claim 3, characterized in that: The preparation method of high-density electrolytic paper comprises the following steps: taking bleached kraft softwood pulp, soaking it in deionized water, beating it to a beating degree of 77-82°SR, and diluting it with first deionized water to obtain liquid one; taking modified cellulose fiber, mixing it in second deionized water, dispersing it, adding it to liquid one, homogenizing it for 2-4 hours, making wet paper, pressing and drying the wet paper, and calendering it to obtain high-density electrolytic paper.
7. The power capacitor according to claim 6, characterized in that: The preparation method of the modified cellulose fiber comprises the following steps: uniformly dispersing the cellulose fiber in a third deionized water, adding a modifier, adjusting the pH of the system to be stable between 10 and 10.5, reacting for 3 to 5 hours, washing the product with deionized water until it is neutral, and drying the product.
8. The power capacitor according to claim 7, characterized in that: The cellulose fibers include first cellulose fibers, second cellulose fibers, and third cellulose fibers.
9. A method for preparing a power capacitor according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: cutting the positive electrode foil and the negative electrode foil and riveting them with the positive guide pin and the negative guide pin; putting the electrolytic paper between the riveted positive electrode foil and the negative electrode foil and winding them to form a core package, injecting electrolyte into the core package, sealing it in an aluminum shell by using colloid particles, and mechanically waisting and sealing it to obtain a semi-finished capacitor; washing the semi-finished capacitor, sleeve it, aging and selecting it, performing secondary aging and selecting it, observing the appearance, and inspecting it in sequence to obtain the capacitor.
10. The method for preparing a power capacitor according to claim 9, characterized in that: The number of layers of the electrolytic paper is 4.
Citation Information
Patent Citations
Method for preparing aluminum electrolytic capacitor with ultra-small volume specially used for energy-saving lamp
CN101667494A
Anode foil formation technology
CN110144612A
Production method and structure of -55 DEG C ultralow-temperature guide pin type safety aluminum electrolytic capacitor
CN112735851A
Production process of ultra-low-thickness electrolytic capacitor paper
CN117090074A